Present‐Day Greenland Ice Sheet Climate and Surface Mass Balance in CESM2. Issue 2 (22nd February 2020) - van Kampenhout, Leonardus; Lenaerts, Jan T. M.; Lipscomb, William H.; Lhermitte, Stef; Noël, Brice; Vizcaíno, Miren; Sacks, William J.; van den Broeke, Michiel R.
Abstract : The response of the Greenland Ice Sheet (GrIS) to a warmer climate is uncertain on long time scales. Climate models, such as those participating in the Coupled Model Intercomparison Project phase 6 (CMIP6), are used to assess this uncertainty. The Community Earth System Model version 2.1 (CESM2) is a CMIP6 model capable of running climate simulations with either one‐way coupling (fixed ice sheet geometry) or two‐way coupling (dynamic geometry) to the GrIS. The model features prognostic snow albedo, online downscaling using elevation classes, and a firn pack to refreeze percolating melt water. Here we evaluate the representation of the GrIS surface energy balance and surface mass balance in CESM2 at 1° resolution with fixed GrIS geometry. CESM2 agrees closely with ERA‐Interim reanalysis data for key controls on GrIS SMB: surface pressure, sea ice extent, 500 hPa geopotential height, wind speed, and 700 hPa air temperature. Cloudsat‐CALIPSO data show that supercooled liquid‐containing clouds are adequately represented, whereas comparisons to Moderate Resolution Imaging Spectroradiometer and CM SAF Cloud, Albedo, and Surface Radiation data set from Advanced Very High Resolution Radiometer data second edition data suggest that CESM2 underestimates surface albedo. The seasonal cycle and spatial patterns of surface energy balance and surface mass balance components in CESM2 agree well with regional climate model RACMO2.3p2, with GrIS‐integrated melt, refreezing, and runoff bracketed by RACMO2 counterparts at 11 and 1 km. Time series of melt, runoff, and SMB show a break point around 1990, similar to RACMO2. These results suggest that GrIS SMB is realistic in CESM2, which adds confidence to coupled ice sheet‐climate experiments that aim to assess the GrIS contribution to future sea level rise. Key Points: The simulation of GrIS climate and SMB in CESM2 compares well to reanalyses and RACMO2 data GrIS‐integrated melt, runoff, and refreezing in CESM2 are bracketed by RACMO2 estimates at 11 and 1 km A break point in SMB is identified at year 1993 ± 8, driven by increased melt and runoff